Preferences for Renal Cell Carcinoma Pharmacological Treatment: A Discrete Choice Experiment in Patients and Oncologists - Fernández, Ovidio; Lázaro-Quintela, Martín; Crespo, Guillermo; Soto de Prado, Diego; Pinto, Álvaro; Basterretxea, Laura; Gómez de Liaño, Alfonso; Etxaniz, Olatz; Blasco, Sara; Gabás-Rivera, Clara; Aceituno, Susana; Palomar, Virginia; et al. (Frontiers in Oncology, 2022)
Introduction: The purpose of this investigation was to explore patients’ and oncologists’ preferences for the characteristics of a pharmacological regimen for patients with advanced renal cell carcinoma (aRCC). Material and methods: Cross-sectional observational study based on a discrete choice experiment (DCE) conducted in Spain. A literature review, a focus group with oncologists and interviews with patients informed the DCE design. Five attributes were included: progression survival gain, risk of serious adverse events (SAEs), health-related quality of life (HRQoL), administration mode, and treatment cost. Preferences were analyzed using a mixed-logit model to estimate relative importance (RI) of attributes (importance of an attribute in relation to all others), which was compared between aRCC patients and oncologists treating aRCC. Willingness to pay (WTP, payer: health system) for a benefit in survival or in risk reduction and maximum acceptable risk (MAR) in SAEs for improving survival were estimated from the DCE. Subgroup analyses were performed to identify factors that influence preference. Results: A total of 105 patients with aRCC (77.1% male, mean age 65.9 years [SD: 10.4], mean time since RCC diagnosis 6.3 years [SD: 6.1]) and 67 oncologists (52.2% male, mean age 41.9 years [SD: 8.4], mean duration of experience in RCC 10.2 years [SD: 7.5]) participated in the study. The most important attribute for patients and oncologists was survival gain (RI: 43.6% vs. 54.7% respectively, p˂0.05), followed by HRQoL (RI: 35.5% vs. 18.0%, respectively, p˂0.05). MAR for SAEs was higher among oncologists than patients, while WTP (for the health system) was higher for patients. Differences in preferences were found according to time since diagnosis and education level (patients) or length of professional experience (oncologists). Conclusion: Patients’ and oncologists’ preferences for aRCC treatment are determined mainly by the efficacy (survival gain) but also by the HRQoL provided. The results of the study can help to inform decision-making in the selection of appropriate aRCC treatment.